IgE epitopes of Ara h 9, Jug r 3, and Pru p 3 in peanut-allergic individuals from Spain and the US - Kronfel, Christina M.; Cheng, Hsiaopo; McBride, Jane K.; Nesbit, Jacqueline B.; Krouse, Rebecca; Burns, Preston; Cabanillas, Beatriz; Crespo, Jesus F.; Ryan, Robert; Simon, Reyna J.; Maleki, Soheila J.; Hurlburt, Barry K. (Frontiers in Allergy, 2023)
Non-specific lipid transfer proteins (LTPs) are well studied allergens that can lead to severe reactions, but often cause oral allergy syndrome in the Mediterranean area and other European countries. However, studies focused on LTP reactivity in allergic individuals from the United States are lacking because they are not considered major allergens. The goal of this study is to determine if differences in immunoglobulin (Ig) E binding patterns to the peanut allergen Ara h 9 and two homologous LTPs (walnut Jug r 3 and peach Pru p 3) between the US and Spain contribute to differences observed in allergic reactivity. Synthetic overlapping 15-amino acid-long peptides offset by five amino acids from Ara h 9, Jug r 3, and Pru p 3 were synthesized, and the intact proteins were attached to microarray slides. Sera from 55 peanut-allergic individuals from the US were tested for IgE binding to the linear peptides and IgE binding to intact proteins using immunofluorescence. For comparison, sera from 17 peanut-allergic individuals from Spain were also tested. Similar IgE binding profiles for Ara h 9, Jug r 3, and Pru p 3 were identified between the US and Spain, with slight differences. Certain regions of the proteins, specifically helices 1 and 2 and the C-terminal coil, were recognized by the majority of the sera more often than other regions of the proteins. While serum IgE from peanut-allergic individuals in the US binds to peptides of Ara h 9 and its homologs, only IgE from the Spanish subjects bound to the intact LTPs. This study identifies Ara h 9, Jug r 3, and Pru p 3 linear epitopes that were previously unidentified using sera from peanut-allergic individuals from the US and Spain. Certain regions of the LTPs are recognized more often in US subjects, indicating that they represent conserved and possible cross-reactive regions. The location of the epitopes in 3D structure models of the LTPs may predict the location of potential conformational epitopes bound by a majority of the Spanish patient sera. These findings are potentially important for development of peptide or protein-targeting diagnostic and therapeutic tools for food allergy.